Indonesian Purple Rice Ferulic Acid as a Candidate for Anti-aging through the Inhibition of Collagenase and Tyrosinase Activities - Dian Siswanto; Ernanin Dyah Wijayanti; Anna Safitri; Fatchiyah Fatchiyah (Indonesian Journal of Chemistry, 2023)
Skin aging is associated with decreased skin firmness and excessive pigmentation, which is caused by the activity of aging enzymes. This process can be prevented with powerful antioxidants from nature, such as ferulic acid which is abundant in rice. This study examines the nutritional content and phytochemicals of Indonesian purple rice and evaluates the bioactivity of ferulic acid as an anti-aging agent. Indonesian purple rice has less fat than black and white rice, more amino acids involved in aging regulation, and a similar phytochemical profile to black and white rice. Indonesian purple rice has a lower concentration of ferulic acid (4.114 ± 0.013 mg/L) than black rice but shows strong reducing power (IC50 9.35 ± 1.95 µg/mL), high anti-tyrosinase (IC50 59.57 ± 3.60 µg/mL), and moderate anti-collagenase activities (IC50 74.18 ± 3.11 µg/mL). This study supports the use of Indonesian purple rice as a promising active ingredient in natural anti-aging cosmetics.